Reflections - Joanne Embree (Canadian Journal of Infectious Diseases)
Ideally, editorials are written one to two months before publication in the Journal. It was my turn to write this one. I had planned to write the first draft the evening after my clinic on Tuesday, September 11. It didn't get done that night or during the next week. Somehow, the topic that I had originally chosen just didn't seem that important anymore as I, along my friends and colleagues, reflected on the changes that the events of that day were likely to have on our lives.